Interaction between IGF-1 polymorphisms and overweight for the risk of pancreatic cancer in Japanese - Nakao, Makoto (e-Century Publishing Corporation, 2011)
Although several reports have described a possible association between insulin-like growth factors-1 (IGF-1) and pancreatic cancer (PC) risk, this association has not been evaluated in the non-Caucasian population. To assess the impact of IGF-1 polymorphisms on PC risk in Japanese, we conducted a case-control study which compared the frequency of ten single nucleotide polymorphisms (SNPs) and haplotypes of IGF-1. SNPs were investigated using the TaqMan method in 176 patients with PC and 1402 control subjects. Exposure to risk factors was assessed from the results of a self-administered questionnaire. Associations and gene-environment interactions were examined using an unconditional logistic regression model. We did not observe any significant main effect of IGF-1 loci, but did find interactions between rs5742714 and past and/or current body-mass index (BMI) status. Among patients with BMI > 25 at age 20, an increased PC risk was observed with the addition of the minor allele for rs5742714 (trend P = 0.048) and rs6214 (P = 0.043). Among patients with current BMI > 25, an increased or decreased PC risk was observed with the addition of the minor allele for rs5742714 (trend P = 0.046), rs4764887 (P = 0.031) and rs5742612 (P = 0.038). Haplotype analysis of IGF-1 showed a significant association among patients who were either or both previously or currently overweight. These findings suggest that IGF-1 polymorphisms may affect the development of PC in the Japanese population in combination with obesity. Further studies to confirm these findings are warranted.